Optimization of Diagnosis, Treatment, and Prevention of Concomitant Exotropia with a Vertical Component - Rustamovna, Abdullaeva Dilorom (American Journal of Biomedicine and Pharmacy, 2025)
Concomitant exotropia with a vertical component is a complex form of strabismus that poses diagnostic and therapeutic challenges. This article explores optimized approaches to the diagnosis, treatment, and prevention of this type of strabismus. Emphasis is placed on comprehensive clinical assessment, the role of imaging, modern surgical techniques, and rehabilitation protocols. Preventive strategies, especially in early childhood, are also discussed. The integration of orthoptic therapy with surgical management and long-term follow-up is critical in achieving optimal ocular alignment and visual function.